A236 METRONIDAZOLE IN THE TREATMENT OF RECURRENT HEPATIC ENCEPHALOPATHY: A CASE SERIES. (1st March 2018) - Amin, A; Shah, D; Cabrera-García, L; Carbonneau, M; Newnham, K; Tandon, P; Abraldes, J
Abstract: Background: Hepatic encephalopathy (HE) affects 50–70% of cirrhotic patients. Lactulose is first-line therapy in HE prevention and in preventing recurrent HE. Rifaximin (RIF) is the next therapeutic choice for HE prevention after two recurrent HE episodes despite lactulose treatment. RIF has been suggested to have the additional benefit of improving circulatory dysfunction in cirrhosis. A special access program (SAP) for RIF was discontinued in January 2014. Due to its high cost, only a few patients could remain on RIF through private insurance. AASLD/EASL guidelines suggest either neomycin or metronidazole (MET) as potential alternatives, but only MET is available in Canada. However, the evidence on MET's efficacy and safety in the treatment of HE is very limited. Aims: The aims of the present study were to describe our experience with MET in patients with recurrent HE, and to assess if treatment with MET was associated with changes in readouts of circulatory and liver function in patients with advanced cirrhosis. Methods: This was a retrospective case-series study including: 1) patients receiving RIF for the prevention of recurrent HE and then switched to MET (250mg PO BID) at the end of the special access program (SAP) (n=5); 2) patients started de novo on MET after the end of the SAP (n=14); and 3) patients who received RIF as a part of the SAP and continued on it (n=12). Treatment was initially limited to 6 months due to the risk of toxicity. Demographics, clinical and laboratory parameters were collected from 3 months before the index date to 6 months after. Results: Table 1 summarizes the characteristics of the patients. During the 6 months of MET treatment, 2 of the 19 patients treated with MET developed a total of 3 episodes of HE. Among the 12 patients continued on RIF, 3 of them developed a total of 3 episodes of HE. During the study follow-up there were no significant changes in the mean creatinine, sodium, bilirubin or albumin in any of the three study groups, or toxicity directly associated with the use of MET. Conclusions: Despite the limited evidence that a case-series can provide, MET appears to be a safe and effective interim alternative for the prevention of recurrent HE in settings with limited access to RIF. Funding Agencies: NoneN/A